The Influence of Social Media Use on Adolescent Sexual Behavior at SMAN 1 Tebing Syahbandar in 2026 - Hamni Nasution; Rotua Sumihar; Novita Br. Ginting (JURNAL KESMAS DAN GIZI (JKG), 2026)
The rapid advancement of information and communication technology has significantly increased social media usage, particularly among adolescents. Social media offers various benefits, including facilitating social interaction, expanding access to information, and providing a platform for self-expression. This study aimed to examine the relationship between social media use and adolescent sexual behavior at SMAN 1 Tebing Syahbandar, Serdang Bedagai Regency, in 2026.This research employed a quantitative design with a cross-sectional approach. The study involved 231 students aged 15–18 years. Data analysis was conducted using univariate analysis to describe the distribution of variables, bivariate analysis with the Chi-square test to assess associations between variables, and multivariate analysis using logistic regression to identify the most influential factors affecting adolescent sexual behavior.The findings revealed that 208 respondents (90.0%) were categorized as having high-risk sexual behavior. The bivariate analysis indicated that the duration of social media use was not statistically associated with adolescent sexual behavior (p = 0.434). However, frequency of use (p = 0.006), intensity of use (p = 0.000), and exposure to sexual content (p = 0.000) were significantly associated with adolescent sexual behavior.The multivariate analysis demonstrated that the intensity of social media use was the most dominant factor influencing adolescent sexual behavior, followed by exposure to sexual content. Overall, these findings suggest that social media use contributes to adolescent sexual behavior, particularly when characterized by high intensity and frequent exposure to sexually explicit content.This study highlights the importance of strengthening digital literacy, enhancing parental supervision, and reinforcing school-based reproductive health education. These efforts are expected to equip adolescents with the skills to use social media wisely and responsibly, thereby minimizing the risk of unhealthy sexual behavior.